SPEECH ACT IN INDONESIAS’ SHAMPOO ADVERTISMENT - Risna Rudiawati; vivi fitria; Trisnendri Syahrizal (PROJECT (Professional Journal of English Education), 2018)
Advertisement as the tool for communicating and promoting a specific product to the customer brings a new phenomenon on the use of language. Every utterance has the function, from a very simple point of view advertisement is objected to making customer buying their product. Illocutionary act as an action via utterance are able to project the main objective of the advertisement, wheatear this advertisement expressing feeling, representing facts, declaring the point of view, promoting question, and promising goal. This research objects to revile the speech act used in Indonesian shampoo advertisement using qualitative study. This use 84 utterances from 5 brand of shampoo. Those 84 utterances were taken from video ads of 5 shampoo product in Indonesia. As the result, Shampoo ads in Indonesia has  % of declarative Speech act, % Commission Speech act, % Representative Speech act, % Expressive Speech act, % Directive Speech act. This result shows that Shampoo product in Indonesia intends to promote their product by declaring their ability in giving the best result for the customer whether it gives a shiner hair, softer hair, stronger hair or others.